Effects of Precooling on Thermoregulation and Performance of Long Distance Runners in Hot Humid Climate - George Abraham3ï€ª, Cicily Pearly Alex4, Sajeev Jos1, Tony Daniel2 (Recent Research in Science and Technology, 2010)
The purpose of the study was to analyze the effects of pre-cooling on thermo regulation and performance of long distance runners in army sports institute. Eight long distance runners of Pune Army Sports institute were selected as subjects. The subjects were selected at random, they were divided in two equal groups for each, and each group will undergo experimental conditions using cooling strategy, during warm up before treadmill test and one control condition with out cooling jacket. The cooling strategy was applied by using cooling jacket for 10 minutes before warm up and during 20 minutes warm up continued by the tread mill test running to exhaustion. The data of criterion variables like core temperature (Tc), Heart Rate (HR), Respiratory Rate (RR) and Blood lactate level (BL) was collected from each subjects before and after each test conditions .The collected data was statistically analyzed by using analysis of variance (ANOVA) with repeated measures and Tukey’s post hoc test were applied to determine the significant differences between the mean. Correlation were also made using Pearson’s Product moment correlation statistics on (1) Core body temperature & environment (2) Total distance run by athletes in control & Experimental condition(3) Total time run by athletes in control and experimental condition .The results of the study showed that there was significant difference in the mean of total time run by the athletes in thread mill before reaching the Exhaustion Level among the experimental condition and controlled condition.